Strategies for Preserving the Use of the Indigenous Language in Kenagarian Kambang Barat, Pesisir Selatan Regency - Delpa D; Yosi Kurnia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Traditional language is an essential element of Minangkabau cultural identity that functions as a medium of communication, cultural transmission, and social identity reinforcement. Globalization, technological development, and changes in communication patterns have contributed to the declining use of traditional language, particularly among younger generations. This study aims to analyze strategies for preserving the use of traditional language in Kenagarian Kambang Barat, Pesisir Selatan Regency. The research employed a descriptive qualitative approach using observation, in-depth interviews with traditional leaders, religious leaders, community leaders, and youth, as well as documentation. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that traditional language remains actively used during customary ceremonies, village deliberations, weddings, religious events, and traditional dispute resolution. However, its daily use has gradually decreased due to the dominance of the Indonesian language, digital media influence, changes in family communication patterns, and limited youth participation in customary activities. Preservation strategies include strengthening the role of families, empowering customary institutions, integrating traditional language into educational activities, involving youth organizations, and utilizing digital media as a platform for cultural education. Collaboration among all community stakeholders is essential to sustaining the traditional language as an important component of Minangkabau cultural identity.